Analysing the Effects of Paid Subscriptions on User Engagement in Social Media Platforms: A Sentiment Analysis Approach - Balcioğlu, Yavuz Selim; Özkoçak, Yelda; Gümüşboğa, Yağmur; Altındağ, Erkut (Journal of Telecommunications and the Digital Economy, 2025)
This study investigates the effects of paid subscriptions on revenue and user engagement on social media platforms, focusing on Instagram. By leveraging Network Externality Theory, Customer Engagement Theory, and Uses and Gratifications Theory, the research explores how paid subscriptions impact network effects, user base growth, and emotional and behavioural engagement. A longitudinal analysis of 146,942 Instagram comments reveals a predominantly positive sentiment towards paid subscriptions, with users expressing high levels of appreciation and satisfaction. The study identifies key themes such as positive engagement, content quality and constructive feedback. Findings suggest that paid subscriptions enhance platform attractiveness and user interaction, driving increased engagement and revenue growth. This research provides valuable insights for platform developers and content creators, highlighting the importance of continuous monitoring and responsiveness to user feedback.